The Dog Louse Heterodoxus spiniger from stray cats in Penang, Malaysia - Norhidayu, S.; Mohd Zain, S.N.; Jeffery, J.; Lewis, J.W. (2012)
Stray cats collected from Georgetown, Penang from 2008 to 2010 were screened for ectoparasites via fine-tooth combing. Two cats from a total 102 examined were infested with the dog louse, Heterodoxus spiniger. Both cats, a juvenile male and female were found in close contact with each other prior to capture. The number of lice ranged from 5 and 14 in the male and female cat respectively. Other ectoparasites recovered included the common cat flea, Ctenocephalides felis, one louse species Felicola subrostratus, one tick species Haemaphysalis bispinosa and one mite species of Listrophoridae. The present study reports for the first time the finding of H. spiniger on cats from peninsular Malaysia.